Event Study: Itama Ranoraya Stock Valuation on Indonesia Stock Exchange during the COVID-19 Pandemic - Posma Sariguna Johnson Kennedy; Ricky Martin Manullang; Chyntia Natasha Sihombing; Laura Magdalena Tampubolon (Universitas Padjadjaran, 2022)
This study aims to analyze investment decisions on one of the pharmaceutical company's shares, PT Itama Ranoraya Tbk, with the code IRRA on the Indonesia Stock Exchange in 2021. The research method used is the event study method (ESM). This research is expected to enrich scientific references for event studies on non-economic events and their impact on the capital market in Indonesia in general. The data used in this research is secondary data, especially from stock movement data and company financial statements. The share acquisition for valuation is only one share from various pharmaceutical industries, namely the IRRA coded stock. The valuation method used is Discounted Cash Flow - Free Cash Flow-to-Firm (DCF-FCFF) analysis. The recommendation is HOLD, with a target price of IDR 2,130 within the next year. The target price indicates a potential increase of 1.91% from the closing price of July 1, 2021